FAKTOR DETERMINAN TERHADAP MINAT PERAWAT DALAM PENGGUNAAN ELECTRONIC MEDICAL RECORD DI IGD RUMAH SAKIT PUSAT PERTAMINA - Mar'atul Isnainyah (2023)
Along with the development of time there are many technological developments. In the world of health, it has also developed a lot in helping to improve the quality of health services. The Emergency Room is the spearhead in a hospital service. Sophisticated technology is needed to improve services. One technology that can be used is Electronic Medical Record (EMR). The success of using EMR cannot be separated from the factors that influence interest in using this technology. This study aims to determine the determinants of emergency room nurses' interest in using EMR. Cross-sectional research design using total sampling technique, the questionnaire used is the Unified Theory of Acceptance and Use of Technology (UTAUT). The results of the sprearman analysis show that the performance expectation factor 0.773, effort expectation 0.788, social influence 0.297, and supporting facility conditions 0.57 show that there is no relationship between nurses' interest in using EMR where the p-value> 0.05. For this reason, the availability of supporting facilities with a system that is easy to use, as well as socialization and training for nurses is expected to help increase nurse interest in using EMR.